The Consolidation of The Colonial State and Resistance in Gorontalo, 1908–1942 - Joni Apriyanto; Yety Rochwulaningsih; Singgih Tri Sulistiyono; Haryono Rinardi (PURBAWIDYA, 2026)
This article focuses on the study of the strengthening of the Dutch colonial state in Gorontalo, the accompanying dynamics of local conflict, and the forms of resistance carried out by nationalist movement groups during the period 1908–1942. The aim of this study is to explain why and how the process of colonial state consolidation took place in Gorontalo, while also analyzing the relationship between repressive colonial policies, local conflicts, and the emergence of resistance by nationalist movements within the context of Indonesia’s national awakening. The method employed in this article is the historical method, which includes the stages of heuristics (source collection), source criticism, interpretation, and historiography, in order to analytically reconstruct colonial dynamics and the socio-political responses of Gorontalo society. The findings of this study indicate that the strengthening of the Dutch colonial state in Gorontalo occurred alongside the implementation of modern administrative systems, economic commercialization, and hegemonic colonial social stratification. These policies not only triggered local conflicts but also opened spaces for political mobilization and education, which were utilized by nationalist movement groups to build resistance, both through organizational activities and collective actions. These findings are significant because they demonstrate that local dynamics in Gorontalo constitute an integral part of Indonesia’s national historical process. The resistance of nationalist movements in Gorontalo represents a local articulation of opposition to colonial hegemony, while simultaneously affirming Gorontalo’s position in the history of the formation of national consciousness and the collapse of Dutch colonial rule.